265TiPKEYNOTE-826: A phase III randomized study of chemotherapy with or without pembrolizumab for first-line treatment of persistent, recurrent, or metastatic cervical cancer. (24th November 2019) - Fujiwara, K; Shapira-Frommer, R; Alexandre, J; Monk, B; Fehm, T; Colombo, N; Caceres, M V; Hasegawa, K; Dubot, C; Li, J J; Stein, K; Keefe, S M; et al.
Abstract: Background: Patients with advanced cervical cancer comprise a high-risk, poor prognostic group. Vascular endothelial growth factor (VEGF) has emerged as a therapeutic target for these patients, though incorporation of the anti-VEGF agent bevacizumab to platinum- and taxane-based chemotherapy (CT) is associated with a modest OS benefit vs CT alone (median OS, 16.8 vs 13.3 mo; hazard ratio, 0.77, 95% CI, 0.62-0.95; P = 0.007; Tewari et al. Lancet. 2017). On the basis of an ORR of 14.3% (95% CI, 7.4-24.1) among 77 pretreated women with PD-L1–positive tumors in the cervical cancer cohort of KEYNOTE-158 (Chung et al. J Clin Oncol. 2019), the PD-1 inhibitor pembrolizumab was granted accelerated approval by the US FDA for patients with PD-L1–positive (combined positive score [CPS] of > 1) cervical cancer who had progressed during or after first-line CT. KEYNOTE-826 (NCT03635567) is a phase 3, randomized, double-blind, multinational study designed to evaluate the efficacy and tolerability of CT with or without pembrolizumab and/or bevacizumab in the first-line setting. Trial design: Eligible patients with recurrent, persistent, or metastatic cervical cancer not previously treated with CT in a recurrent or metastatic setting who are not amenable to curative treatment will be randomized 1:1 to CT + pembrolizumab 200 mg or placebo every 3 weeks. The CT regimen (paclitaxel 175 mg/m 2 + cisplatin 50 mg/m 2 or carboplatin AUC 5, with or without bevacizumab 15 mg/kg) will be selected by the investigator before randomization. Stratification will be performed by metastasis status at diagnosis, planned bevacizumab use (yes/no), and tumor PD-L1 CPS (<1, 1 to < 10, or ≥ 10). Treatment will continue for ≤35 cycles (∼2 years) or until disease progression, unacceptable toxicity, or voluntary patient withdrawal. Primary endpoints are PFS per RECIST v1.1 (assessed by blinded independent central review) and OS. Secondary endpoints are ORR, duration of response, 12-month PFS, patient-reported quality of life, and safety. Enrollment is currently ongoing. Clinical trial identification: NCT03635567. Legal entity responsible for the study: Merck & Co., Inc. Funding: Funding for this study was provided by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA. Disclosure: K. Fujiwara: Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Chugai Pharma; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Eisai; Advisory / Consultancy, Research grant / Funding (institution): Merck Sharpe & Dohme Corp.; Advisory / Consultancy, Research grant / Funding (institution): Pfizer; Honoraria (self), Advisory / Consultancy, Research grant / Funding (institution): Taiho Pharmaceutical; Advisory / Consultancy: Takeda; Honoraria (self): Bayer; Honoraria (self): Daiichi Sankyo; Honoraria (self): Janssen Oncology; Honoraria (self): Kyowa Hakko Kirin; Honoraria (self): Lilly Japan; Honoraria (self): Nippon Kayaku; Honoraria (self), Research grant / Funding (institution): Ono Pharmaceutical; Honoraria (self), Research grant / Funding (institution): Zeria Pharmaceutical; Research grant / Funding (institution): GlaxoSmithKline; Research grant / Funding (institution): Kaken Pharmaceutical; Research grant / Funding (institution): Immunogen; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Oncotherapeutics. R. Shapira-Frommer: Honoraria (self): MSD Oncology; Honoraria (self): Bristol-Myers Squibb; Honoraria (self): Novartis; Honoraria (self): Roche; Honoraria (self): AstraZeneca; Advisory / Consultancy: Vascular Biogenics; Advisory / Consultancy: Clovis Oncology. J. Alexandre: Honoraria (self): Roche/Genentech; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy, Travel / Accommodation / Expenses: Novartis ; Honoraria (self): Sanofi/Aventis; Honoraria (self), Advisory / Consultancy: Ipsen; Advisory / Consultancy: Roche; Advisory / Consultancy: Sanofi; Research grant / Funding (institution), Travel / Accommodation / Expenses: Janssen. B. Monk: Advisory / Consultancy: AbbVie; Advisory / Consultancy: Advaxis; Advisory / Consultancy: Agenus; Advisory / Consultancy: Amgen; Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Biodesix; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Conjupro; Advisory / Consultancy: Genmab; Advisory / Consultancy: Gradalis; Advisory / Consultancy: ImmunoGen; Advisory / Consultancy: Immunomedics; Advisory / Consultancy: Incyte; Advisory / Consultancy: Janssen/Johnson&Johnson; Advisory / Consultancy: Mateon (formally Oxigene); Advisory / Consultancy: Merck; Advisory / Consultancy: Myriad; Advisory / Consultancy: Perthera; Advisory / Consultancy: Pfizer; Advisory / Consultancy: Precison Oncology. T. Fehm: Honoraria (self), Advisory / Consultancy: Novartis; Honoraria (self), Advisory / Consultancy: Roche; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Pfizer. N. Colombo: Honoraria (self), Advisory / Consultancy: Roche/Genentech; Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self): TESARO, Inc.; Honoraria (self), Advisory / Consultancy: PharmaMar; Advisory / Consultancy: Clovis Oncology; Advisory / Consultancy: Pfizer; Advisory / Consultancy: MSD Oncology; Advisory / Consultancy: Takeda; Advisory / Consultancy: TESARO, Inc.; Advisory / Consultancy: BioCad. K. Hasegawa: Honoraria (self), Research grant / Funding (self): Daiichi-Sankyo; Honoraria (self), Advisory / Consultancy: Merck Sharpe & Dohme Corp.; Honoraria (self): Chugai; Honoraria (self): AstraZeneca; Research grant / Funding (self): Yakult Honsha; Research grant / Funding (self): Pfizer. J.J. Li: Travel / Accommodation / Expenses, Full / Part-time employment: Merck & Co., Inc.; Travel / Accommodation / Expenses, Spouse / Financial dependant: Celgene. K. Stein: Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc.; Shareholder / Stockholder / Stock options: Novartis. S.M. Keefe: Travel / Accommodation / Expenses, Shareholder / Stockholder / Stock options, Full / Part-time employment: Merck & Co., Inc. K. Tewari: Honoraria (self): TESARO, Inc.; Honoraria (self): Clovis Oncology; Advisory / Consultancy, Speaker Bureau / Expert testimony, Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche/Genentech; Speaker Bureau / Expert testimony: AstraZeneca ; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Merck; Research grant / Funding (institution): AbbVie; Research grant / Funding (institution): Morphotek; Research grant / Funding (institution): Regeneron. All other authors have declared no conflicts of interest.